Escalating crisis in the eurozone: The case for conditional debt relief for Greece (Statement No. 40) - David Veredas; Niels Thygesen; Tom Berglund; Reinhard H. Schmidt; Franco Bruni; Harald Benink; Kern Alexander; Santiago Carbo-Valverde; Rosa Lastra; Clas Wihlborg (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2015)
In this statement the European Shadow Financial Regulatory Committee (ESFRC) is advocating a conditional relief of Greek's government debt based on Greece meeting certain targets for structural economic reforms in areas such as its labor market and pensions sector.The authors argue that the position of the European institutions that debt relief for Greece cannot be part of an agreement is based on the illusion that Greece will be able to service its sovereign debt and reduce its debt overhang after implementing a set of fiscal and structural reforms. However, the Greek economy would need to grow at an unrealistig level to achieve debt sustainability soley on the basis of reforms.The authors therefore view a substantial debt relief as inevitable and argue that three questions must be resolved urgently, in order to structure debt relief adequately: First, which groups must accept losses associated with debt relief. Second, how much debt relief should be offered. Third, under what conditions should relief be offered.
Keywords: 330; Greek crisis; structural reforms; debt sustainability